DASAR KEISLAMAN SEBAGAI AGAMA RAHMATAN LILALAMIN - Abdul Wahab Syakhrani; Muhammad Rivaldi Yudistira (CV. Adiba Aisha Amira, 2022)
Islam Rahmatan lil'alamin is Islam whose presence in the midst of people's lives is able to create peace and love for humans and nature. The implementation of mercy for the universe has extended to almost all parts of the world. Etymologically, Islam means peace, while rahmatan lil `alamin means `love for the universe. So what is meant by Islam Rahmatan lil'alamin is Islam whose presence in the midst of people's lives is able to create peace and love for humans and nature